Plantas daninhas gramíneas interferindo no eucalipto: Efeitos da distância da convivência no crescimento inicial das plantas - Graat, Y. [UNESP]; Rosa, J. O. [UNESP]; Nepomuceno, M. P. [UNESP]; Carvalho, L. B.; Alves, P. L.C.A. [UNESP] (FapUNIFESP (SciELO), 2015)
Two experiments were carried out to evaluate the initial plant growth of Eucalyptus urograndis growing in coexistence with Urochloa decumbens and U. ruziziensis. In 100-L box, one plant of U. decumbens or U. ruziziensis grew in coexistence with one plant of E. urograndis clones C219H or H15, respectively, in the distances of 0, 5, 10, 15, 20, 25, 30, 35, and 40 cm from the crop. After 30, 60, 90 (both clones), and 150 days (just for H15), growth characteristics were evaluated. Plants of both clones, growing in weed-free situations, showed a better growth and development than plants that grew in weedy situations, independently of the distance, having the highest plant height, stem diameter, dry mass of stem, and dry mass of leaves. As the same way, the number of branches, number of leaves, and leaf area of the clone C219H were similarly affected. Urochloa ruziziensis reduced the dry mass accumulation of stem and leaves by the rate of 0.06 and 0.32 g per plant, respectively, per each centimeter growing nearest to the crop, while U. decumbens reduced by 0.03 and 0.14 g per plant. The interference of U. decumbens and U. ruziziensis with E. urograndis is more intense when weedy plants grow in short distances from the crop.
Grass weeds interfering with eucalypt: Effects of the distance of coexistence on the initial plant growth
Keywords: Eucalyptus urograndis; Urochloa decumbens; Urochloa ruziziensis; Weed competition